Relationship between resting VO2max consumption, functional independence, and physical activity levels in mothers of children with immobile cerebral palsy - Tekin, Fatih; Bilek, Furkan (Bayrakol Medical Publisher, 2021)
Aim: In the current literature, there is no study investigating the relationship between oxygen consumption in children with Cerebral Palsy (CP) and the physical activities of their parents. In this study, we aimed to investigate the relationship between resting VO2max consumption and functional independence and physical activity levels in mothers of children with immobile CP. Material and Methods: Thirty cerebral palsied cases (F:16, M:14) with a mean age of 6.63 +/- 2.68 years (3-12 years) were included in the study with their mothers. Registration forms were filled out for each case. Children were evaluated with the Functional Independence Scale for Children (WeeFIM). Resting VO2max measurements were performed with the Cosmed Fitmate Protm device. International Physical Activity Questionnaires (IPAQ) were completed for mothers. Results: There are no statistically significant differences between the mean resting VO2max values of quadriplegic and diplegic CP cases (p>0.05), and there are no statistically significant differences in mean resting VO2max values of the cases with CP in terms of gender (p>0.05). There is a significant correlation between resting VO2max values of patients with CP and their mothers' physical activity levels (p<0.05). Likewise, there is a significant correlation between functional independence levels in daily living activities of patients with CP and their mothers' physical activity levels (p<0.05). Discussion: Physical activity levels of mothers with CP are lower in all areas compared to mothers who do not have a disabled child. Resting VO2max values and functional independence of children with CP are better in mothers with high physical activity levels.
Keywords: Cerebral palsy; Physical activity; Functional independence; Oxygen consumption